The Combination of Deep Breathing, Isometricity, and Religious Prayer on Reducing Blood Pressure in Elderly Parents with Hypertension - Indana Zulfa Yunaida; Joni Haryanto; Andri Setiya Wahyudi (Indonesian Journal of Global Health Research, 2025)
Hypertension treatment therapy needs to be supported by non-pharmacological therapy because it has fewer side effects, one of which is exercise, but so far it has not been widely done by hypertension sufferers. The study was to analyze the effect of the combination of NADA ISME RELIGI (deep breathing, isometrics and religious prayers) on reducing blood pressure in elderly with hypertension. A quasi-experimental study with a pretest-posttest with a control group design was used in 66 elderlies with hypertension recruited using purposive sampling. The research variables were the combination of NADA ISME RELIGI and blood pressure. Data analysis using paired sample t-test and independent t-test. The results of inferential testing showed that in the intervention group the pre and post-test values of blood pressure were p = 0.000 (p <0.05), so it can be concluded that the combination intervention of RELIGIOUS NADA ISME has a significant effect on blood pressure in hypertension sufferers. The combination of RELIGIOUS NADA ISME (Deep Breathing, Isometric and Religious Prayer) can reduce blood pressure in the elderly with hypertension, as evidenced by the results of research in the intervention group showing a decrease in blood pressure.